Morel Lavallée Lesion – A case report and review of literature - Pikkel, Y.Y. (Int J Surg Case Rep, 2020)
INTRODUCTION: Morel-Lavallée lesion (MLL) is an uncommon entity, by which shearing forces result in a closed degloving lesion. This can result in an infected hematoma and lead to a life-threatening situation. PRESENTATION OF CASE: We present a case of a 59-year-old patient who presented to our emergency department. This patient had a crushing injury, and later was found to have an infected MLL. The patient was treated with surgical drainage, and 2 split thickness skin grafts. The patient fully healed. DISCUSSION: We review the current literature regarding MLL and diagnostic tools in order to accurately and rapidly diagnose this often-missed entity. Special emphasis is given to the treatment of MLL, with the current knowledge as reflected in the literature. CONCLUSIONS: It is important for caregivers to know the diagnostic steps and pitfalls of this elusive diagnosis in order to diagnose and treat MLL quickly, before it turns into a life-threatening state for the patient.